ANALISIS DAMPAK RASIO PROFITABILITAS SEBAGAI INDIKATOR KINERJA PERUSAHAAN (STUDI KASUS: PT BANK SYARIAH INDONESIA TAHUN 2020-2024) - Rahman, Anggi Meisya; Pramana, Pandu; Ausaa, Khairul; Saputra, Arief Dwi; Wirman, Wirman; Rahmiyanti, Sev (Taksasila Edukasi Insani, 2025)
The study focuses on analyzing PT Bank Syariah Indonesia (BSI) Tbk.'s financial performance from 2020-2024, specifically examining profitability ratios like Net Profit Margin, Return on Asset, and Return on Equity. The research highlights the significance of measuring profitability in evaluating Islamic banking operations post-merger and pandemic challenges. Using a quantitative approach and data from BSI's financial statements, the analysis includes calculating financial ratios, trend analysis over five years, and benchmarking against industry standards. The study aims to offer insights into BSI's profitability, identify factors influencing its financial performance, and provide valuable information for management, investors, regulators, and stakeholders to make informed decisions regarding BSI's performance and sustainability in the Islamic banking sector.Keywords : NPM, Profitability, Ratio, ROA, ROE.